Jian-Pi-Yi-Shen Formula Ameliorates Oxidative Stress, Inflammation, and Apoptosis by Activating the Nrf2 Signaling in 5/6 Nephrectomized Rats - Zhou, Fanyuan; Zou, Xiaohu; Zhang, Jing; Wang, Ziwei; Yang, Yajun; Wang, Dongtao (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is an increasing global public health problem, with high morbidity and mortality. Jian-Pi-Yi-Shen (JPYS) formula is a representative Traditional Chinese medicine formula in the treatment of CKD, which is widely used in clinical practice in China. However, the underlying mechanism has not been well elucidated. In the present study, we measured the markers of apoptosis, inflammation and oxidant stress and Nuclear factor erythroid 2-relared factor 2 (Nrf2) signaling to investigate the effects of JPYS formula on renal function and fibrosis and its molecular mechanism in an established animal model of 5/6 nephrectomized (5/6Nx) rats. The results demonstrated that JPYS formula exerted a significant preventive effect on renal dysfunction and fibrosis, based on analysis of correlative parameters such as urinary protein, Scr, BUN, glomerular sclerosis index and tubulointerstital fibrosis score, as well as renal histopathology and ultrastructural pathology of CKD rats. JPYS formula also induced down-regulation of gene expression associated with fibrosis, such as TGF-β, and type I, III, IV collagen. Moreover, JPYS formula showed a significant protective effect in suppressing cell apoptosis according to results of apoptotic indexes, including decreased gene expression of Bax, caspase 3, caspase 9, increased gene expression of Bcl-2, and the number of TUNEL positive cells. JPYS formula also ameliorated the activation of NF-κB - mediated inflammatory pathway, as manifested by down-regulation of gene expression of TNF-α, IL-1β, IκBα, NF-κB p65, MCP-1, CXCL1, COX-2 and iNOS in the kidney. Our evidence also suggested that JPYS formula ameliorates oxidative stress by virtue of promoting antioxidant function according to results of antioxidant index as indicator of GSH, SOD, CAT and GPx, and abating excessive accumulation of the reactive oxygen species biomarkers, including ROS, TBARS, 8-Oxo-dG and MDA. The data also suggested that JPYS formula reversed down-regulation of HO-1and Nrf2 level and up-regulation of Keap1 expression. Together, our data highlight that JPYS formula relieves renal oxidative injury mediated by activation of Nrf2 signaling through inhibiting inflammation and apoptosis in CKD rats.